Baseflow and lowflow of catchments covered by various old teak forest areas - Tyas Mutiara Basuki; Esa Bagus Nugrahanto; Irfan Budi Pramono; Wahyu Wisnu Wijaya (Brawijaya University, 2019)
Drought has become a severe disaster faced by several regions in Java, Indonesia due to land cover changes including forest conversion and the increase in air temperature. In this regards, the availability of forests related to lowflow has been a controversial debate. Forest in Java is dominated by teak; however, the hydrological teak forest has not been well known. Therefore, a research has been undertaken to know the baseflow and low-flow of teak catchments covered by various old teak forest areas. The research areas were in Blora District, Central Java, Indonesia. Data of2008-2015 from five catchments with areas of 3.38, 13.47, 20.14, 27.79, 64.80, and 69.20 ha and covered by old teak forests of 82, 82, 74, 70, and 53% of the catchment were analyzed. In this study, baseflow is the delayed flow from bank storage, and low-flow is stream flow in the dry season. The results showed that baseflow is affected by the percentage of old teak plantation areas, rainfall and antecedent soil moisture condition. Areas of the old teak plantation and the baseflow show negative and non-linear correlation. High low-flow occurs in the catchments with the percentage of old teak plantation about 74 to 70%.